Aplicación de normas de convivencia y autonomía en niños de la Institución Educativa Inicial N° 362 Santa Rosa, distrito de Yavarí 2022 - Pacaya Fasabi, Claudy Tavit (2023)
The study's central question was, "Is there a correlation between the degree to which children in the Yavari District 2022's Initial Educational Institution No. 362 Santa Rosa, aged five, apply the rules of coexistence and their degree of autonomy?" and generally speaking: Discuss the ways in which the youngsters at Yavari District Initial Educational Institution No. 362 Santa Rosa have been applying the rules of coexistence and independence so far in the year 2022. According to the objective, the type of relational research was considered and as procedures the cross-sectional, field design was applied. and bivariate. The 79 children of the educational institution were the population and sample at the same time, and to the observation and observation sheets as a technique and instruments for data collection Conclusion: there is a relationship between the application level of the rules of coexistence with the achievement of learning in autonomy in children because in 19 (24.1%) who have expected autonomy achievement if rules of coexistence apply, in the 57 (72.2%) children with autonomy achievement in process, 2.5% (n =2) do not apply rules of coexistence, sometimes in 45.6% (n=36) and if they apply in 24.1% (n=19). The 3 (3.8%) children who initially show achievement of autonomy do not apply the rules of coexistence in the classroom. The greater the application of the rules of coexistence, the greater the development of autonomy in children.